FIS-ranking and carving turn force production profile - Keränen, T.; Ihalainen, S.; Hynynen, E.; Salo, T. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: In the slalom ski race, the skier loses velocity during the turns and increases velocity between them (Haugen et al 2007). Because the turn phases are longer than the gliding ones, proper carving turn technique plays a crucial role. The skier controls the trajectory of the skis with force production and on-edge ski angles, trying to avoid excess velocity decrease. The purpose of this study was to evaluate the differences between high and low ranked skiers' force productions to the skies during the carved turn.